2017
DOI: 10.5194/hess-21-2649-2017
|View full text |Cite
|
Sign up to set email alerts
|

Scaled distribution mapping: a bias correction method that preserves raw climate model projected changes

Abstract: Abstract. Commonly used bias correction methods such as quantile mapping (QM) assume the function of error correction values between modeled and observed distributions are stationary or time invariant. This article finds that this function of the error correction values cannot be assumed to be stationary. As a result, QM lacks justification to inflate/deflate various moments of the climate change signal. Previous adaptations of QM, most notably quantile delta mapping (QDM), have been developed that do not rely… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(132 citation statements)
references
References 51 publications
1
130
0
1
Order By: Relevance
“…However, Switanek et al (2017) showed this assumption of a stationary error correction function to be invalid, and as a result, the altering of the raw model projected changes to precipitation and temperature was found to be unjustified. SDM, in contrast, does not rely on a stationary error correction function, but rather attempts to best preserve the raw model projected changes across the entire distribution.…”
Section: Error Correctionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Switanek et al (2017) showed this assumption of a stationary error correction function to be invalid, and as a result, the altering of the raw model projected changes to precipitation and temperature was found to be unjustified. SDM, in contrast, does not rely on a stationary error correction function, but rather attempts to best preserve the raw model projected changes across the entire distribution.…”
Section: Error Correctionmentioning
confidence: 99%
“…The novel method Scaled distribution mapping (SDM) is used to bias correct the model precipitation and temperature data time series (Switanek et al, 2017). The commonly used bias correction method of quantile mapping (Wood et al, 2004;Piani et al, 2010;Themeßl et al, 2011;Teutschbein and Seibert, 2013) assumes that error correction functions can be treated as stationary from one time period to another.…”
Section: Error Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the equidistant quantile mapping (EQM) approach (Li et al, 2010;10 Srivastav et al, 2014;Sachindra et al, 2014) was employed to bias-correct the ICRA precipitation time-series. EQM is an adaptation of the original quantile mapping method that accounts for non-stationarity in the moments of the biased time-series and helps to preserve changes in the cumulative distribution function of the precipitation data that may have occurred over time (Switanek et al, 2017;Cannon et al, 2015). To evaluate the effectiveness of the bias-correction procedure, the R 2 correlation score was calculated between the bias-corrected ICRA data and the measured AWS1 data.…”
Section: Precipitationmentioning
confidence: 99%
“…High-quality observational datasets of surface downwelling radiation are of interest in many fields of climate science, including energy budget estimation (Kiehl and Trenberth, 1997;Trenberth et al, 2009;Wild et al, 2013) and climate model evaluation (Garratt, 1994;Ma et al, 2014;Wild et al, 2015). As part of so-called climate or meteorological forcing datasets such as those generated within the Global Soil Wetness Project (GSWP; Zhao and Dirmeyer, 2003), at Princeton University (Sheffield et al, 2006), and within the Integrated Project Water and Global Change (WATCH; Weedon et al, 2011), the longwave and shortwave components of surface downwelling radiation (abbreviated as rlds and rsds or just longwave and shortwave radiation in the following) are used to correct model biases in climate model output (Hempel et al, 2013;Iizumi et al, 2017;Cannon, 2017) and drive simulations of climate impacts, for example (Müller Schmied et al, 2016;Veldkamp et al, 2017;Chang et al, 2017;Krysanova and Hattermann, 2017;Ito et al, 2017).…”
Section: Introductionmentioning
confidence: 99%